(Re) Designing fashion contextual studies: a generative view of socio-semiotics in creative higher education (Revista de Ensino em Artes, Moda e Design, 2021)
The article presents the case for pedagogical approaches in Arts and Design Higher Education that are not informed exclusively by Pedagogy, but growing around Socio-semiotics which ceases to be a theory of critical analysis, to become a tool explored in its generative potential to construct, in reverse, practices that will be put into discourse. From programme design to the delivery of face to face and online sessions with students, the programme constituting the main case of this work was idealised, designed, and delivered utilising the principles of Greimas’ semiotics (1986, 1987, 2002; GREIMAS & COURTÉS, 1993) concerning the analysis of discourses, and the theories of interactions developed by Landowski (2004, 2005, 2009, 2010) and Oliveira (2002, 2013). The bridge created between those theories and Freire’s (1970) Critical Pedagogy permitted to explore different modes of presence in the classroom, which transformed the roles of tutor and student, as well as the contents of the course. Seeing Higher Education beyond economic exchanges welcomed the construction of an attitude toward knowledge that surpasses the idea of “skill transfer”, cultivating adjustments which aim at the union between different subjects, resulting in the teaching of theory reaching beyond the writing of essays and becoming an integral part in the making of design. Through the transformations of interactions between the tutor, students, and the course contents, the model presented in the article invites a reflection on the importance of semiotic concepts in the process of constructing educational practices that “make sense”.
Keywords: Sociossemiótica; Educação em Moda; Discursivização